2013
DOI: 10.1007/s11235-013-9725-y
|View full text |Cite
|
Sign up to set email alerts
|

Passive filterless core networks based on advanced modulation and electrical compensation technologies

Abstract: In this paper, the filterless optical network concept is presented and explored through a number of filterless solution examples. In the first part, the filterless network concept is presented and analyzed through a comparative case study. In the second part, the filterless network design problem is defined and a filterless network design tool based on metaheuristics is presented. In the third part of this presentation, filterless network solutions are proposed for a number of core network topologies and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As losses due to the network elements can be compensated thanks to the presence of SOAs, this switching option can be envisioned also for applications in filterless optical networks. This would represent a cost-effective solution [15], as active reconfigurable components are eliminated or minimized using passive optical elements as combiners or/and splitters to interconnect the fiber links and to add or drop channel wavelengths at the nodes. Some advantages are expected for these networks such as simplified maintenance or reconfigurability.…”
Section: Soa Technology For Optical Metro Network Nodesmentioning
confidence: 99%
See 3 more Smart Citations
“…As losses due to the network elements can be compensated thanks to the presence of SOAs, this switching option can be envisioned also for applications in filterless optical networks. This would represent a cost-effective solution [15], as active reconfigurable components are eliminated or minimized using passive optical elements as combiners or/and splitters to interconnect the fiber links and to add or drop channel wavelengths at the nodes. Some advantages are expected for these networks such as simplified maintenance or reconfigurability.…”
Section: Soa Technology For Optical Metro Network Nodesmentioning
confidence: 99%
“…In particular, we consider an SOA-based switching node with and without filtering elements. In the last case, the switching functionalities are performed by the SOAs and can also find application in filterless optical networks [15]. Filterless optical networks are simple network architectures based on passive splitters and combiners avoiding optical filters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Filterless solutions have been proposed for terrestrial and submarine network topologies. The first studies were focused on regional and core network applications [6][7][8][9][10]. Unsurprisingly, comparative cost analyses in terrestrial networks have shown significant savings are achievable in the filterless network solutions due to replacement of switching and filtering elements by simple fiber couplers.…”
Section: Performance Analysis and Design Trade-offsmentioning
confidence: 99%